As geo-grafias na biblioteca escolar: olhares dos professores de Geografia do municipio de Porto Nacional – TO sobre as potencialidades das bibliotecas escolares - Ferreira, Hosana Moura (Universidade Federal do Tocantins, 2023)
This research analyzed the perception of geography teachers about the potential of school libraries from Porto Nacional (TO) from the support of their pedagogical practices. In this way, an exploratory research was carried out, using the questionnaire remotely, by Google Docs platform as the main data instrument colection. This paper has also a qualitative dimension and presentes the Geography teachers form public and private schools from Porto Nacional as their subjects. The literature review was made around the teachers’s trainning issues, practice of teaching geography, school library themes, and the library as a geographical space. The results indicated the presence (or not) of the school libraries in our city. The frequency and motivations of geography teachers to use the school Libraries, and plus of that, we draw a profile of our subjects and also obtained a little about his teaching practice. It is understood that this theme is important due to every school have (or should) a library, and it is advisable to know and use these school spaces in the best possible way. Thus, the investigation points to the importance of the entire school community is encouraged to reflect on the potential of the school library in teaching-learning. Suggested that school managers that they are partners in the search for the mitigation of the challenges that cause the low attendance of geography teachers in this spaces and that these, in turn, also seek for possible solutions.